Extraction of keratin from waste chicken feathers using sodium sulfide and L-cysteine - Pourjavaheri, Firoozeh; Ostovar Pour, Saeideh; Jones, Oliver A. H.; Smooker, Peter M.; Brkljača, Robert; Sherkat, Frank; Blanch, Ewan W.; Gupta, Arun; Shanks, Robert A. (Elsevier Ltd, 2019)
Keratin was extracted from different segments of disposable waste chicken feathers (CF) including the whole feathers, calamus/rachis (β-sheet) and barbs/barbules (α-helix), using sodium sulfide and L-cysteine. The yield of extracted keratin from sodium sulfide and L-cysteine was ˜88% and ˜66% respectively. The mass ratio of feathers to reducing agent was 1:20 and the reaction temperature was 40 °C for 6 h. Concentration of keratin extracted by each method was measured using the Bradford assay. The protein extracted from each feather section was characterised using sodium dodecyl sulfate-polyacrylamide gel electrophoresis, vibrational spectroscopy including FTIR and Raman, nuclear magnetic resonance, and thermogravimetry. These results confirmed the keratin structures after each extraction methods. The study showed that α-helix and ß-sheet based keratin could be extracted from CF using sodium sulfide and L-cysteine with high yields. This is the first report of CF keratin extraction using L-cysteine.